The hydrological functions of Ultisols: Study of biopores and oil palm waste application impact in oil palm plantations - Sunarti, Sunarti; Endriani, Endriani; Azani, Muhammad Raidan (Brawijaya University, 2025)
Ultisol is one type of soil available for the development of oil palm plantations in Indonesia. Oil palm development is faced with negative perceptions due to the degradation of soil and regional hydrological functions. The purpose of this research was to evaluate the impact of the application of biopores filled with various types of oil palm waste on the hydrological function of Ultisols with oil palm plantations. This research used an experimental method designed by creating eight experimental plots consisting of seven plots with biopores filled with various types of oil palm waste and one plot without biopores. The research data included organic carbon content, bulk density, porosity, permeability, infiltration, and water retention of soil. Data were obtained through analysis of soil samples in the laboratory and field measurements. Data were analyzed descriptively and by regression analysis with a confidence level of 95% (? = 0.05). The research results showed that the application of biopores with various oil palm wastes was able to improve soil characteristics and hydrological functions of Ultisols in oil palm plantations. The application of biopores with a combination of Mucuna bracteata, empty oil palm fruit bunches, oil palm pruning leaves, and oil palm shell biochar showed the best effect on improving soil characteristics and hydrological functions. Improvement of soil characteristics was correlated with improvement of hydrological function in Ultisols. Therefore, biopores filled with oil palm waste can be recommended as an integrative soil and water conservation technology for controlling the hydrological functions of Ultisols in oil palm plantations.